The effect of different conjugated structures in main ligand on the photophysical properties for a series of iridium(III) complexes from a theoretical perspective. (1st April 2018) - Han, Deming; Liu, Chuanzhi; Lv, Shuhui; Zhao, Lihui; Zhao, Henan
Graphical abstract: The effect of different conjugated structures in main ligand on the electronic and photophysical properties of a series of iridium(III) complexes has been investigated by using the density functional theory and time-dependent density functional theory calculations. Abstract: The electronic structure and photophysical properties of five iridium(III) complexes have been studied using the density functional theory (DFT) and time-dependent density functional theory (TDDFT) methods. The influence of different conjugated structures on their photophysical properties has been explored. Ionization potentials, electron affinities and reorganization energy have also been obtained to evaluate the charge transfer and balance properties between hole and electron. The lowest energy emissions from the CAM-B3LYP level for these complexes are localized at 472, 503, 523, 635 and 699 nm, respectively. The theoretical investigation would be useful to design potential phosphorescent materials for application in the organic light-emitting diodes.